Defining and teaching veterinary professionalism - Mossop, Liz (2012)
Despite extensive research and discussion around the notion of medical professionalism, veterinary professionalism is an understudied area. The aim of this study was to define the concept of veterinary professionalism and analyse the hidden curriculum of a new veterinary school, in order to produce a new curriculum of professionalism. This study used a constructivist grounded theory method to develop the definition. An iterative approach, using interviews and focus groups, collected information from a range of stakeholders including veterinary surgeons, professional bodies, veterinary nurses and clients. Sampling was theoretical and concluded when theoretical saturation had been reached. An analysis of the hidden curriculum of a new veterinary school was also undertaken using a cultural web model to perform a thematic analysis of focus group narratives from staff and students. The outcomes from both studies were combined to develop a curriculum of veterinary professionalism. The normative definition of veterinary professionalism produced places the attribute of balance as the central component. Veterinary surgeons are constantly managing the requirements and expectations of their clients, the animals under their care, society and the veterinary practice that provides their employment. The ability to balance these demands and therefore demonstrate professionalism is helped by attributes which are: efficiency, technical competence, honesty, altruism, communication skills, personal values, autonomy, decision making, manners, empathy, confidence and acknowledgement of limitations. The components of the veterinary school’s hidden curriculum emerged within the framework of the cultural web and the development of professional identity was a consistent theme. The school’s central paradigm was found to be a community that is hard working and friendly. Routines and rituals were readily identified, as were both positive and negative role models. The curriculum of veterinary professionalism produced is an integrated, spiral curriculum involving strategies such as early clinical experience and critical event analysis to guide student reflections and shape their development as professionals. Four core professional skills of communication, ethical reasoning, reflective practice and learning skills are central to the curriculum. These are used to reinforce the values and behaviours included in the definition of professionalism. The definition of veterinary professionalism should also contribute to discussions around the position of the profession in society. The central behaviour of balancing responsibilities between clients, animals, the practice and society appears to be uniquely positioned, and may have application in other professionalism contexts. The presented curriculum is a good starting point for any veterinary school wishing to teach veterinary professionalism, alongside consideration of their hidden curriculum.